Educação não formal: um estudo de caso a partir do Parque Estadual Paulo César Vinha - Calenzani, Cecília Elias (2023)
The present research has as its theme non-formal education from the Paulo César Vinha State Park (PEPCV) and its object of study was the conceptions about nonformal education of potential PEPCV attendees. In this sense, we seek to investigate, through PEPCV, whether teachers from surrounding schools, visitors and employees, point to some conception of non-formal education, in addition to characterizing the current scenario of use of PEPCV by these subjects and investigating whether they use it recognize as an educational space. Therefore, this is a qualitative research, since the data obtained will be treated considering discursive principles, taking into account that these subjects carry with them a set of ideals, methodologies and experiences that express their conceptions of non-formal education. Regarding the methodological design, this research is characterized as a case study. As an instrument for obtaining data, documentary consultation, observation and semistructured interviews were used, instruments that will constitute verbal and non-verbal communication (gestures, intonations and hesitations). The research subjects consisted of teachers from schools surrounding PEPCV, as well as their employees and visitors (external and internal community). Data analysis was carried out through content analysis, from the perspective of Franco (2005), as an analytical device. The analyzes were divided into thematic axes and sub-axis and, from them, we can say that the majority of participating teachers did not intend to pursue a teaching career when they began their training. Furthermore, few had contact with activities carried out outside the formal environment during their graduation, and none declared having received training for non-formal education during this period. With regard to the general objective of this research, all subjects were able to make some consideration about non-formal education. Of the nine subjects interviewed, six presented conceptions that are close to the concepts proposed by the theoretical references used in this research. Regarding the characterization of the PEPCV usage scenario, only two of the teachers stated that they had already carried out activities with the PEPCV. In the activities carried out by PEPCV, we identified, in two fields of work: the activities that employees carry out in schools surrounding PEPCV; and environmental monitoring activities, offered to groups that want adequate guidance. Furthermore, all the subjects investigated in this research consider PEPCV as an educational space with numerous attractions for consolidating teaching relationships. In this way, the paths adopted in the research contribute to discussions about the concepts and dimensions of nonformal education, by seeking to understand its influence on the integral formation of individuals.